FORMULASI DAN ANALISA KUALITAS SPORT DRINK BERBASIS STROBERI DAN MULBERRY SEBAGAI SUMBER ANTIOKSIDAN ATLET ENDURANCE - Luthfi, Alifah; Surmita, Surmita; Saleky, Yohannes Willihelm; Rosmana, Dadang; Isdiany, Nitta (Poltekkes Kemenkes Bandung, 2023)
Endurance athletes potentially have dehydration because the activity that carried out continuously for a long time.The activity can increase oxygen consumption that may lead to the production of free radicals that have a bad effect for health .To neutralize free radicals in the body , athletes need to consume antioxidant .Research aims to asses the differences in formulation of strawberries and mulberry organoleptic ( color, aroma , taste and viscosity) in the sports drink and also potassium, sodium , antioxidant activity and osmolality content in selected sports drinks . Design research used is experimental. Based on statistical tests, there are no significant differences of the formulation on the color , aroma , taste and viscosity. Test the preferences by the 30 disciplinary shows that F3 (75% strawberries: 25% mulberry) is most favored with average score color ( 5.8 ), aroma ( 5.8 ), taste ( 5.37 ) and viscosity ( 5.67 ). In 1 kg sport of drink (F3) containing 704.9 mg sodium, 165 mg potassium, antioxidant activity ( ic50 ) 1323.34 ppm and osmolality 327 mOsmol / kg.